Modelling long-lived health care workflow transactions - Meli, Christopher (2014)
Due to the increasing automation of health care, health care work ows have received signi cant attention over the last few years. This paper discusses the di erences between typical business processes and health care work ows, and introduces a layered architecture suitable for health care work ow models.We present a rules-based approach for mod- elling long-lived health care work ow transactions, and we discuss a set of transactional integrity rules speci c to the work ow patterns found in traditional business processes and show how these rules can be used to design health care work ows with transactional characteristics.